Phosphoprotein inhibitor CPI-17 specificity depends on allosteric regulation of protein phosphatase-1 by regulatory subunits - Eto, Masumi (National Academy of Sciences, 2004)
Inhibition of myosin phosphatase is critical for agonist-induced contractility of vascular smooth muscle. The protein CPI-17 is a phosphorylation-dependent inhibitor of myosin phosphatase and, in response to agonists, Thr-38 is phosphorylated by protein kinase C, producing a >1,000-fold increase in inhibitory potency. Here, we addressed how CPI-17 could selectively inhibit myosin phosphatase among other protein phosphatase-1 (PP1) holoenzymes. PP1 in cell lysates was separated by sequential affinity chromatography into at least two fractions, one bound specifically to thiophospho-CPI-17, and another bound specifically to inhibitor-2. The MYPT1 regulatory subunit of myosin phosphatase was concentrated only in the fraction bound to thiophospho-CPI-17. This binding was eliminated by addition of excess microcystin-LR to the lysate, showing that binding at the active site of PP1 is required. Phospho-CPI-17 failed to inhibit glycogen-bound PP1 from skeletal muscle, composed primarily of PP1 with the striated muscle glycogen-targeting subunit (G(M)) regulatory subunit. Phospho-CPI-17 was dephosphorylated during assay of glycogen-bound PP1, not MYPT1-associated PP1, even though these two holoenzymes have the same PP1 catalytic subunit. Phosphorylation of CPI-17 in rabbit arteries was enhanced by calyculin A but not okadaic acid or fostriecin, consistent with PP1-mediated dephosphorylation. We propose that CPI-17 binds at the PP1 active site where it is dephosphorylated, but association of MYPT1 with PP1C allosterically retards this hydrolysis, resulting in formation of a complex of MYPT1·PP1C·P-CPI-17, leading to an increase in smooth muscle contraction.